الأخلاقيات المهنية في مؤسسات التمويل الأصغر الإسلامية - Dato Muhammad Muda; Muhammad Aunurrahim; Hani Yahya (TSAQAFAH, 2011)
The role of professional ethics is indeed significant in the local and global market realities, in which most of organizations and financial institution try to survive right in the middle of  the current tight competition in the business, particularly in gaining trust and financial sources from societies as well as customers and employees. This brief  study focused on the scope of professional ethics that govern the activities of general Islamic institutions which are working in the field of microfinance. Those institutions are really in desperate need of these ethics that maintain the growth and sustainability, and then could protect the rights of the poor who are dealing with it. In the other hand this research also reviewed the ten of the most important ethical principles that should be a general framework for any proposed model of the code of Islamic microfinance ethics, to match transactions with these institutions with the principles of Islamic morality as well as the technical rules governing the work of  these institutions.  This research found and came out with a batch of  results and recommendations which will hopefully contribute to the consolidation of the theoretical framework for study as well as enhancing the practical side of ethics. market realities, in which most of organizations and financial institution try to survive right in the middle of the current tight competition in the business, particularly in gaining trust and financial sources from societies as well as customers and employees. This brief study focused on the scope of professional ethics that govern the activities of general Islamic institutions which are working in the field of microfinance. Those institutions are really in desperate need of these ethics that maintain the growth and sustainability, and then could protect the rights of the poor who are dealing with it. In the other hand this research also reviewed the ten of the most important ethical principles that should be a general framework for any proposed model of the code of Islamic microfinance ethics, to match transactions with these institutions with the principles of Islamic morality as well as the technical rules governing the work of these institutions.  This research found and came out with a batch of results and recommendations which will hopefully contribute to the consolidation of the theoretical framework for study as well as enhancing the practical side of ethics.